Oldest Near-Complete Acanthodian: The First Vertebrate from the Silurian Bertie Formation Konservat-Lagerstätte, Ontario - Burrow, Carole J.; Rudkin, David (PLOS ONE, 2014)
Background The relationships between early jawed vertebrates have been much debated, with cladistic analyses yielding little consensus on the position (or positions) of acanthodians with respect to other groups. Whereas one recent analysis showed various acanthodians (classically known as ‘spiny sharks’) as stem osteichthyans (bony fishes) and others as stem chondrichthyans, another shows the acanthodians as a paraphyletic group of stem chondrichthyans, and the latest analysis shows acanthodians as the monophyletic sister group of the Chondrichthyes. Methodology/Principal Findings A small specimen of the ischnacanthiform acanthodian Nerepisacanthus denisoni is the first vertebrate fossil collected from the Late Silurian Bertie Formation Konservat-Lagerstätte of southern Ontario, Canada, a deposit well-known for its spectacular eurypterid fossils. The fish is the only near complete acanthodian from pre-Devonian strata worldwide, and confirms that Nerepisacanthus has dentigerous jaw bones, body scales with superposed crown growth zones formed of ondontocytic mesodentine, and a patch of chondrichthyan-like scales posterior to the jaw joint. Conclusions/Significance The combination of features found in Nerepisacanthus supports the hypothesis that acanthodians could be a group, or even a clade, on the chondrichthyan stem. Cladistic analyses of early jawed vertebrates incorporating Nerepisacanthus, and updated data on other acanthodians based on publications in press, should help clarify their relationships.